Obesity and type 2 diabetes as chronic inflammation: how does the cytokine evidence align? - Bhatia, Karishma; Gupta, Vikas Kumar; Upadhyay, Sanjeev K. (Frontiers in Endocrinology, 2026)
Obesity is a global epidemic and a major risk factor for several non-communicable diseases. Systemic inflammation is believed to be involved in obesity and obesity-induced diabetes type 2, which alters adipose tissue homeostasis. Cytokines, the key mediators of inflammation, play a central role in this inflammatory state and have been extensively studied for their role in obesity and diabetes type 2. Therefore, blood and adipose tissue levels of cytokines have been a subject of intense investigation over the last two decades. Several studies reveal the role of cytokines and their profiles in the obese population. These studies have reported the significance of altered levels and patterns of several cytokines and their association with clinical parameters in obese and type 2 diabetics. This review examines population-based studies to evaluate whether cytokine profile consistently reflect chronic inflammation in obesity and type 2 diabetes. It highlights cytokines that show robust associations across ethnic and geographic cohorts. While majority of cytokines are frequently elevated in both conditions, their predictive value remains unclear. On the contrary we do find inflammatory cytokines like IL-1β which shows an association with diabetes type 2 but not obesity while IL-6 is more closely associated with obesity than diabetes. Anti-inflammatory cytokines IL-10 and IL-4 cannot be linked to either conditions. The study underscores the need for longitudinal and mechanistic studies to determine whether cytokine profiling could be used as an early diagnostic or prognostic tool.